DEVELOPMENT OF AN E-LEARNING SYSTEM TO SUPPORT DISTANCE LEARNING IN JUNIOR HIGH SCHOOLS - Asrul Sani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The COVID-19 pandemic has forced education systems around the world to adapt to unexpected conditions, including the implementation of distance learning (PJJ). Junior High Schools face special challenges in this transition due to limited infrastructure and resources. This research aims to develop an optimized e- learning system to support distance learning in junior high schools, with a focus on affordability, ease of use, and pedagogical effectiveness. This system development method involves needs analysis, design, implementation, and evaluation of the system with the active participation of teachers, students, and parents. The research results show that the e-learning system developed can increase student engagement, facilitate access to diverse and interactive learning materials, and support teachers in managing virtual classes. System evaluation was carried out through satisfaction surveys, analysis of student learning performance, and user feedback, which showed significant improvements in the effectiveness of distance learning. This research concludes that the development of e-learning systems tailored to the specific needs of junior high schools can be an effective solution to overcome the challenges of distance learning, while providing opportunities for pedagogical innovation in future education.